Determinant Factors of Islamic Bank Financial Performance and Competitive Advantage As Moderating Variables in Islamic Banks in Indonesia. - Ahmad BADAWI; Lucky NUGROHO; Nurul HIDAYAH (Indonesia Strategic Sustainability, 2023)
The era of the industrial revolution 4.0 requires every company to be able to adapt by making changes and improving financial and non-financial performance. In addition, to reduce the very severe impact of the threat of competitors, Islamic banking must increase its competitive advantage with various strategies that must be achieved, especially related to organizational performance. Islamic banks compete with conventional banks, which are more advanced in products and technology. This research refers to the Technological Readiness Level (TKT) at level 3, which proves the concept of functions and important characteristics analytically and experimentally. This study aims to analyze the factors that affect the financial performance of Islamic banks moderated by competitive advantage variables. The variables observed in this study were the ratio of NPF, NOM, ROA and BOPO. The variable was moderated by the company's competitive advantage (AUE). The method used is quantitative using multiple regression. The data used are annual reports published from 2018 to 2020. The results show that the NOM and NPL variables have an insignificant effect, while the BOPO variable has a significant negative effect. Meanwhile, the competitive advantage variable cannot moderate the effect of NOM, NPL and BOPO on ROA (Company Financial Performance). Therefore, this study contributes that in improving its financial performance, Islamic banking still needs to focus on the amount of income earned to fulfill its obligations Operational Costs and Operating Income (BOPO) in addition to NOM and NPL. Meanwhile, competitive advantage must be improved to improve Islamic banks' performance.